MYOB Accounting Computer Teaching Material Version 23 - Jessica Jessica; Muhammad Taufik (ConCEPt - Conference on Community Engagement Project, 2023)
Education activities have returned to normal since the end of the endemic in 2022. However, since students have been unable to engage in face-to-face education due to the prolonged online learning course, they have been shifting their educational activities to regain this experience. This community service consists of preparing materials to contribute to positive learning experiences. It was conducted at Maitreyawira Vocational High School in Tanjungpinang. We have compiled an e-book that is accounting computerized for service and trade companies: MYOB Version 23 application. As well as educational videos and essays, this e-book also contains PowerPoint presentations and multiple-choice questions. This community service meets curriculum standards in vocational high schools and can be used by teachers, students, and educational supervisory bodies.